2004
DOI: 10.3310/hta8340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of abnormal uterine bleeding: comparison of three outpatient procedures within cohorts defined by age and menopausal status

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 41 publications
2
67
0
6
Order By: Relevance
“…However, in randomized trials from Scotland, the Tao Brush (Cook Medical; Bloomington, IN; USA) was found to be superior to the Pipelle catheter in obtaining a satisfactory endometrial sample (72% to 43%) 56,57 (Class 1b). Endometrial cytology with liquid-based techniques has also been described to have a high sensitivity for carcinoma, but it has not been compared with blind sampling 58 (Class 3).…”
Section: Investigation Of Women With Postmenopausal Uterine Bleeding:mentioning
confidence: 99%
“…However, in randomized trials from Scotland, the Tao Brush (Cook Medical; Bloomington, IN; USA) was found to be superior to the Pipelle catheter in obtaining a satisfactory endometrial sample (72% to 43%) 56,57 (Class 1b). Endometrial cytology with liquid-based techniques has also been described to have a high sensitivity for carcinoma, but it has not been compared with blind sampling 58 (Class 3).…”
Section: Investigation Of Women With Postmenopausal Uterine Bleeding:mentioning
confidence: 99%
“…1 According to hospital episode statistics, UK 10,559 hysterectomies were performed due to menorrhagia in 2002. 2 A patient preference study in the UK showed that approximately 85% women would consider a 50:50 chance of treatment failure to avoid a hysterectomy.…”
Section: 5005/jp-journals-10033-1193mentioning
confidence: 99%
“…De acuerdo a lo examinado y valorando los estudios randomizados controlados y publicados últimamen-te (3,32), existirían esfuerzos para lograrlo. Sin embargo, a falta de protocolos definidos, existen algunas recomendaciones y conceptos generales que pueden aplicarse al estudio del endometrio sintomático:…”
Section: Conclusionesunclassified
“…Menos frecuentes en general son el cáncer endometrial y otros tumores malignos, los cuales son excepcionales en mujeres jóvenes. Es necesario estudiar 3.000-4.000 mujeres con alteraciones de flujos rojos menores de 40 años para encontrar un cáncer endometrial (3). En contraste, alrededor del 10% de las metrorragias postmenopáusicas presenta un cáncer uterino, principalmente de endometrio, existiendo series que oscilan entre 5-60% de los casos, dependiendo de los factores de riesgo presentes (4).…”
Section: Introductionunclassified